2022
DOI: 10.1093/nar/gkac430
|View full text |Cite
|
Sign up to set email alerts
|

Additional principles that govern the release of pre-ribosomes from the nucleolus into the nucleoplasm in yeast

Abstract: During eukaryotic ribosome biogenesis, pre-ribosomes travel from the nucleolus, where assembly is initiated, to the nucleoplasm and then are exported to the cytoplasm, where assembly concludes. Although nuclear export of pre-ribosomes has been extensively investigated, the release of pre-ribosomes from the nucleolus is an understudied phenomenon. Initial data indicate that unfolded rRNA interacts in trans with nucleolar components and that, when rRNA folds due to ribosomal protein (RP) binding, the number of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 84 publications
(78 reference statements)
1
16
0
Order By: Relevance
“…However, our finding that NPM1 phase separation is more strongly impacted by interactions with rRNA as opposed to R-rich linkers suggests that additional factors may contribute to the observed phenotype. Our results also support that nucleolar release requires major architectural changes that occur with installation of the 5S RNP and formation of the CP, as previously preposed 7,11,18 . Indeed, although the exact function of the CP is still under investigation, it is thought to coordinate maturation of LSU functional centers 42,43 and mediate intersubunit bridges 44,54 , making its assembly a critical quality control checkpoint.…”
Section: Discussionsupporting
confidence: 90%
“…However, our finding that NPM1 phase separation is more strongly impacted by interactions with rRNA as opposed to R-rich linkers suggests that additional factors may contribute to the observed phenotype. Our results also support that nucleolar release requires major architectural changes that occur with installation of the 5S RNP and formation of the CP, as previously preposed 7,11,18 . Indeed, although the exact function of the CP is still under investigation, it is thought to coordinate maturation of LSU functional centers 42,43 and mediate intersubunit bridges 44,54 , making its assembly a critical quality control checkpoint.…”
Section: Discussionsupporting
confidence: 90%
“…Along these lines, in vitro experiments showed a preferential partitioning of protein‐free bacterial rRNA but not mature ribosomal subunits into droplets formed by human NPM (Riback et al , 2020 ). Furthermore, a similar model has recently been proposed based on bioinformatic analyses of cryo‐EM structures, which revealed that earlier nucleolar ribosomal precursors contain more unstructured rRNA regions as well as RBFs with predicted intrinsically disordered regions compared to nucleoplasmic subunit assembly intermediates, and both these elements could contribute to nucleolar retention of subunits (LaPeruta et al , 2022 ).…”
Section: Nucleolar Pre‐60s Biogenesismentioning
confidence: 86%
“… 24 , 25 Finally, the GC contains various proteins that assist in further rRNA processing and binding to ribosomal proteins (r-proteins), ultimately forming nearly complete RSUs, which then move into the nucleoplasm and the cytoplasm. 22 , 26 , 27 The size of the compartments suggests that rRNA processing and folding in the GC are the ratelimiting steps for RSU assembly.…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 31 The transfer of rRNA into and out of the GC is linked to the thermodynamics that drives its phase separation—the effective interaction valency of rRNA decreases as it is assembled into ribosomal subunits, resulting in their eventual thermodynamic expulsion. 15 , 27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation